2007
DOI: 10.1080/00914030600873485
|View full text |Cite
|
Sign up to set email alerts
|

Solid State NMR Study ofCouma utilisSeeds

Abstract: This article studies the seed of sorva (Couma utilis) that is a native fruit of Amazons State, in Brazil. Sorva seed components were analyzed by 1 H and 13 C using solid state high resolution nuclear magnetic resonance (NMR) spectroscopy, because they are important nuclei to be used to evaluate plant seeds. High resolution 1 H NMR ( 1 H HRMAS) with magic angle sample spinning (MAS), and 13 C NMR using MAS and particularly 13 C NMR with cross-polarization (CP) and MAS are techniques that allow the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…From the analyses of these NMR signals the majority of components of the latex is derived from: cisisoprene, saturated and unsaturated fatty acids and triacylglycerides esters. As minor components terpenoid compounds were detected and the structure of acyl lupeol ester [2] was identified. The same type of components has been characterized in a similar sample, studied before [2][3][4]15].…”
Section: The Evaluation Of Constituents By Solution Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…From the analyses of these NMR signals the majority of components of the latex is derived from: cisisoprene, saturated and unsaturated fatty acids and triacylglycerides esters. As minor components terpenoid compounds were detected and the structure of acyl lupeol ester [2] was identified. The same type of components has been characterized in a similar sample, studied before [2][3][4]15].…”
Section: The Evaluation Of Constituents By Solution Nmrmentioning
confidence: 99%
“…Natural latexes are complex emulsion in which many substances, such as proteins, polysaccharides, sugars, oils, gums and cis-1,4polyisoprene can be found as major constituents. The latex extracted from Brosimum parinarioides tree found in Amazônia crops is frequently used as food for humble people and it is also used as a popular medicine for treating tuberculosis and asthma [1][2][3][4]. Since its uses were known by the scientific community, some studies about this latex started, but no study was done deeply to know the major components present in these types of sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, fundamental studies about the chemical characteristics of Leite de Amapá have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] Particularly, NMR analyses have been employed successfully to characterize the chemical composition of latexes, using different pulse sequences in high and low magnetic fields. [2][3][4][10][11][12][13][14][15] Based on the previous remarks, the main objective of the present work was to monitor the stability of the Brosimum parinarioides latex at storage conditions at ambient temperature for a period of twelve months. In order to do that, low-field NMR analyses were used to determine the hydrogen relaxation parameters and monitor the stability of the latex.…”
Section: Introductionmentioning
confidence: 99%